Pedophilia: Definition, classifications, criminological and neurobiological profiles, and clinical treatments. A complete review - Giulio Perrotta (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2020)
This work focuses on the topic of pedophilia by reconstructing with a critical review all the main etiological theories proposed in the literature, focusing in particular on the clinical, psychological and neurobiological elements, to conclude that the multifactorial solution is the best possible proposal to account for clinical, psychological, and socio-environmental causes.